Analisis Ketrampilan Berpikir Tingkat Tinggi Mahasiswa Berdasarkan Teori Anderson dan Krathwohl Dalam Mengembangkan Media Pembelajaran Matematika - Tutik Herawati (Jurnal Pendidikan Matematika:Judika Education, 2022)
The purpose of this study was to describe the analysis of higher order thinking skills of STKIP PGRI Jombang students based on Underson and Krathwohl's theory in developing mathematics learning media. This research is a type of qualitative descriptive research. The subjects of this study consisted of 27 students who were divided into 6 groups. Data collection techniques in this study used the main instrument and supporting instruments. The validity of the data using triangulation of sources. Based on the results of research and data analysis obtained that; 1) Students' high-level thinking skills in developing learning media, including high-order thinking modifikatif models, namely changing the shape of a product so that it becomes attractive and more practical, 2) Students develop mathematics learning media based on the problems found, namely helping teachers in conveying messages subject matter to students to make it easier to understand, more interesting, and more fun, 3) The level of high-level thinking of students in developing learning media is very high because they are able to come to the stage of creating, namely designing learning media that are ready to be used or published. Keywords: Higher Order Thinking, Mathematics Learning Media